Enhanced optical, dielectric, and non-Ohmic properties in Ta-doped Bi2/3Cu3Ti4O12 ceramics - Xue, Renzhong; Zhao, Liuyang; Liu, Xiaosong; Wang, Haiyan; Zhu, Xiang; Xiao, Yifan; Yuan, Chunyu; Cao, Binbin; Chen, Ziyang; Li, Tao; Dai, Haiyang (Solid state sciences, 2024)
In this paper, Ta-doped Bi2/3Cu3Ti4O12 (BCTO) ceramics are prepared by solid-state method. Phase structure, microstructure, optical, dielectric, and non-Ohmic properties of all samples are systematically investigated. Cu/Ta-rich phases at grain boundaries (GB) together with defects affect the microstructure, causing grain size and compactness to increase first and then decrease. Moreover, Ta doping increases the optical band gap of BCTO from 4.03 to 4.25 eV as well as the GB activation energy and GB barrier. An increase in dielectric constant (Ɛr), nonlinear coefficient (α) and breakdown field (Eb), and a decrease in the dielectric loss (tanδ) are observed in Ta-doped BCTO ceramics. The improvement in dielectric and non-Ohmic properties can be attributed to the internal barrier layer caused by GB Schottky barrier structure. In particular, Bi2/3Cu3Ti3.95Ta0.05O12 ceramic exhibits the high Ɛr of ∼45997 and the low tanδ of ∼0.035 at 10 kHz along with α of ∼5.62, and Eb of ∼3.45 kV/cm. The temperature-independent (-110-210 °C) dielectric response confirms that temperature stability of specimens increases with doping. These results suggest that improved optical, dielectric, and non-Ohmic properties in Bi2/3Cu3Ti4O12 can be achieved simultaneously via defect engineering. [Display omitted] •The high Ɛr of ∼45997, low tanδ of ∼0.035, α of ∼5.62, and Eb of ∼3.45 kV/cm are obtained in Bi2/3Cu3Ti3.95Ta0.05O12 ceramic.•The Eg increased to 4.25 eV for Bi2/3Cu3Ti3.9Ta0.1O12 ceramic as a result of enhanced structural defects.•Cu/Ta-rich phases at grain boundary together with defects affect the electrical properties in Bi2/3Cu3Ti4-xTaxO12 ceramics.•The improvement in dielectric and non-Ohmic properties via defect engineering can be applied to IBLC model caused.